Stingless bee honey adding butterfly pea flower kombucha on broiler carcass and cholesterol content - Salvia; Fati, Nelzi; Syahrul Hasibuan, Ali (Politeknik Negeri Jember, 2025)
This study evaluated the effect of incorporating stingless bee honey (Trigona spp.) into butterfly pea flower (Clitoria ternatea L.) kombucha in drinking water on cholesterol levels, abdominal fat, and carcass yield in broilers. A completely randomized design with five treatments (T0: control; T1-T4: kombucha with 2%, 3%, 4%, and 5% stingless bee honey) and four replicates were used. Treatments were administered through drinking water for two weeks. Results showed that honey-enriched kombucha significantly reduced cholesterol levels, with the best result observed in T4 (95±4.63 mg/100 g). Abdominal fat decreased and carcass percentage increased, although not statistically significant. These findings suggest that stingless bee honey-enriched kombucha has potential as a natural feed additive to produce healthier broiler meat, likely mediated through enhanced antioxidant activity and inhibition of HMG-CoA reductase.